2010
DOI: 10.1111/j.1440-1681.2010.05460.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, metabolic syndrome, adipocytes and vascular function: A holistic viewpoint

Abstract: SUMMARY1. Obesity is a metabolic disease of pandemic proportions largely arising from positive energy balance, a consequence of sedentary lifestyle, conditioned by environmental and genetic factors. Several central and peripheral neurohumoral factors (the major ones being the anorectic adipokines leptin and adiponecin and the orexigenic gut hormone ghrelin) acting on the anorectic (pro-opiomelanocortin and cocaine-and amphetamine-regulated transcript) and orexigenic (neuropeptide Y and agouti generelated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 116 publications
(254 reference statements)
2
66
0
4
Order By: Relevance
“…These findings go with previous findings of Achike et al [65]; Kitagawa et al [54]; Srinivasan et al [43]; She et al [64].…”
Section: Discussionsupporting
confidence: 82%
“…These findings go with previous findings of Achike et al [65]; Kitagawa et al [54]; Srinivasan et al [43]; She et al [64].…”
Section: Discussionsupporting
confidence: 82%
“…Work-related activities declined, whereas leisure time is dominated by television/computer programs and other physically inactive pursuits (Popkin, 2001). The vicious obesity cycle begins with excess adipose leading to chronic low grade inflammation that results in insulin resistance (IR) along with hypertension, atherosclerosis, dyslipidemia and type 2 diabetes mellitus (T2DM), which are consistent findings of metabolic syndrome (MetS) (Achike et al, 2011). Studies have shown that obesity can be linked to lower ghrelin concentrations in obese individuals (Groschl et al, 2005).…”
Section: Food Addiction and Obesity: Health Problemssupporting
confidence: 50%
“…Metabolic syndrome (MetS) is defined as "a combination of clinical disorders that increase the risk for diabetes and cardiovascular disease, including atherosclerosis, stroke and hypertension" (Achike et al, 2011). The components of MetS include abdominal fat, atherogenic dyslipidemia, hypertension, pro-inflammatory state, pro-thrombic state and IR with or without glucose intolerance (Grundy et al, 2004).…”
Section: Food Addiction and Obesity: Health Problemsmentioning
confidence: 99%
“…[3][4] Similarly obesity is considered a risk factor for insulin resistance, cardiovascular and related diseases. [5][6] Patients with T2DM commonly experience dyslipidaemia contributing to the burden of the cardiovascular mortality.…”
mentioning
confidence: 99%